THE READINESS ANALYSIS OF BLENDED LEARNING IN FLORES UNIVERSITY - Kristina Sara; Ferdinandus Lidang Witi; Anastasia Mude (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
This research aims to know the readiness of blended learning in Flores University area especially in the study program of Information System. This research used a survey research approach with 113 people for the sample. The instrument that was used for this research is the questionnaire of the Likert scale. To analyze the data, this research uses factor analysis in the readiness of adopted learning by Aydin and Tasci. The result of this research were: (1) normally test result showed that all the data are normally distributed because each variable was more than 0,05. (2) The point of KMO MSA was 0,533>0,50 and the point of Barlett's Test of Sphericity (sig.) was 0,000<0,05, it means that the factor analysis can continue. (3) The value of MSA for all variables was >0,50, it means the factor analysis is fulfilled. (4) The extraction value for all the variables was >0,50. So it can be concluded that all the variables are used to explain the factor. (5) The value of Eigenvalues component 1 was 1,858> 1, so it becomes a factor of 1 and can explain 46.453% of the variation. Meanwhile, the value of Eigenvalues component 2 is 1,225>1 so it becomes a factor of 2 and can explain 30,633% of the variation. (6) from the two factors formed, it was feasible to summarize the four variables analyzed. This means that the four variables have the readiness to carry out blended learning at Flores University.